Clinical manifestations and outcomes of HSK following corneal transplantation - Wu, Dan; Huang, Hui; Zheng, Min; Chen, Qi; Zhou, Zhou; Jiang, Li; Li, Yuanhua; Liu, Yiyun; Ma, Baikai; Chen, Guoqing; Huang, Yujun; Cen, Fengping; et al. (Frontiers in Medicine, 2025)
PurposeTo investigate the clinical manifestations and outcomes of herpes simplex keratitis (HSK) infection following corneal transplantation.MethodsThis retrospective study analyzed medical records of patients who underwent corneal transplantation at the People’s Hospital of Guangxi Zhuang Autonomous Region between January 2018 and March 2024, with a minimum follow-up period of 1 year. The study examined post-transplantation herpes simplex virus (HSV) infections, including the timing of HSV infection, HSK classification, clinical manifestations, and outcomes.ResultsA total of 411 patients (corresponding to 411 eyes) were followed up. Among them, 88 cases (21.41% of the 411 cases) were diagnosed with or suspected of HSK before corneal transplantation. Of these 88 cases, 13 cases (14.77% of the 88 cases) developed recurrent HSK after surgery (8 cases underwent corneal transplantation during the acute phase, and 5 cases during the scarring phase). There were 323 cases with no evidence of HSK before corneal transplantation, among which 27 cases (8.36% of the 323 cases) developed new-onset HSK after corneal transplantation. Among all 411 patients, a total of 40 cases (9.73% of the 411 cases) developed HSK after corneal transplantation, with 26 cases (26 eyes) (65% of the 40 cases) developing HSK within 1–3 months post-surgery. Regarding HSK types, epithelial HSK occurred in 11 cases (27.5% of the 40 cases), all of which achieved corneal transparency with regular use of antiviral medication. Stromal necrotizing HSK occurred in 8 cases (20% of the 40 cases), with 2 cases developing corneal nebula, 5 cases developing corneal macula, and 1 case requiring repeat corneal transplantation due to near-perforation. Combined epithelial, stromal, and endothelial HSK occurred in 17 cases (42.5% of the 40 cases), with 1 case developing corneal nebula, 4 cases developing corneal macula, 10 cases developing corneal leucoma, and 2 cases requiring repeat corneal transplantation due to corneal perforation. Endothelial HSK occurred in 4 cases (10% of the 40 cases), with 2 cases achieving grade 0 corneal transparency and 2 cases achieving grade 2 corneal transparency.ConclusionThe first 1–3 months following corneal transplantation is a peak time for HSK. Regular follow-up is essential for all patients post-surgery. For those with a history of HSK, vigilance for HSK is critical, while timely diagnosis and differentiation of HSK are crucial for non-HSK patients. When administering systemic antiviral therapy, it is important to adjust the frequency and intensity of steroid treatments promptly to prevent irreversible graft opacity.